Identifying Core Indicators of Relapse in Clients Undergoing Cognitive Behavioral Therapy for Depression: A Qualitative Study - Gökçay , Kemal; Ceyhan , Murat (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The objective of this study was to explore and identify the core indicators of relapse in clients who have completed cognitive behavioral therapy (CBT) for depression.Methods and Materials: This qualitative study employed a thematic analysis approach based on semi-structured interviews. Twenty-one participants (12 female, 9 male) aged between 23 and 54 years, all of whom had previously undergone a full course of CBT for depression, were recruited from mental health centers in Turkey. Participants were selected through purposive sampling and interviews were continued until theoretical saturation was reached. Data collection involved individual interviews lasting 45–75 minutes, which were audio-recorded, transcribed verbatim, and supplemented with field notes. NVivo 14 software was used to assist with systematic coding, organization, and analysis of the data.Findings: Thematic analysis revealed three overarching categories of relapse indicators. The first, emotional and cognitive triggers, included rumination, negative thinking, cognitive distortions, emotional dysregulation, and loss of therapy skills application. The second, behavioral and lifestyle indicators, encompassed withdrawal, disturbances in sleep and appetite, decline in daily functioning, maladaptive coping strategies, and abandonment of healthy routines. The third, social and interpersonal factors, involved family and relationship strain, lack of social support, stigma and shame, work and academic pressures, and interpersonal sensitivity.Conclusion: Relapse in depression following CBT is a multifaceted process involving the interplay of cognitive-emotional vulnerabilities, behavioral patterns, and social stressors. Early identification of these indicators, combined with booster interventions, aftercare programs, and personalized relapse-prevention planning, may enhance the sustainability of treatment gains.